The metrication of cans in the Philippine setting - Chua, Josephine Ang; Gomez, Ma. Theresa L. (1978., 1978)
Interviews were conducted in order to ascertain and verify the problems and objectives of the can-making industry as regards to metrication. Also, an analysis of re-tooling cost was made. Retooling and die cost were very costly due to several reasons. It varies widely depending upon: volume of production and existing mode of manufacture. Much expenses will be required to acquire new machinery, equipment, parts and supplies calibrated in metric units before switchover to metrication can be brought about. Also, some suggestions and recommendations to facilitate this changeover were given.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Tin cans; Container industry -- Philippines